The Mediating Impact of New Product Innovativeness on the Relationship between Learning Orientation and New Product Performance in Thailand ISO 1900 Industry - Sirivariskul, Nirusa (International Review of Management and Marketing, 2019)
This research examined between the mediating impact of new product innovativeness on the relationship between learning orientation and new product performance. A survey questionnaire from was used to collect data from 62 firms in Thailand.The results indicated that new product innovativeness fully mediates the relationship between learning orientation and new product performance. This finding suggests that manufacturing should develops learning orientation as a competitive factor for new product innovativeness and new product performance. Finally, the study provides a discussion on the academics and practitioners for future research. This research examined the mediating impact of new product innovativeness on the relationship between learning orientation and new product performance. A survey questionnaire form was used to collect data from 62 firms in Thailand.The results indicated that new product innovativeness fully mediates the relationship between learning orientation and new product performance. This finding suggests that manufacturing should develop learning orientation as a competitive factor for new product innovativeness and new product performance. Finally, the study provides a discussion on the academics and practitioners for future research. Keywords: Learning Orientation, New Product Innovativeness, New Product Performance. JEL Classifications: D1, L2 DOI: https://doi.org/10.32479/irmm.8840